Development of Ceramic Materials for the Manufacture of Bricks with Stone Cutting Sludge from Granite - Terrones Saeta, Juan María; Suárez Macías, Jorge; Corpas Iglesias, Francisco Antonio; Korobiichuk, Valentyn; Shamrai, Volodymyr (MDPI, 2024)
The manufacture of bricks for building purposes consumes large quantities of virgin materials, such as clay. On the other hand, the ornamental stone processing industry produces a huge amount of stone cutting sludge in its process. Therefore, this study presents the development of ceramic materials for the manufacture of bricks with stone cutting sludges, more specifically from granite. For this purpose, the physical properties of the stone cutting sludge and the chemical composition were mainly analyzed. Subsequently, different groups of ceramic samples were conformed and sintered with various combinations of clay and of stone cutting sludges. The conformed samples were evaluated with different physical tests and with the compressive strength test. The addition of stone cutting sludges to the ceramics reflected the creation of a material with lower density and higher porosity. The compressive strength of the different groups reflected a maximum allowable percentage of stone cutting sludges incorporation of 70%. Therefore, ceramic materials were developed with stone cutting sludges, developing a sustainable, lighter material with acceptable mechanical and physical characteristics. Avoiding the deposition of a polluting waste in a landfill and at the same time avoiding the extraction of new virgin materials.
Keywords: stone cutting sludge; mining waste; ceramic; brick; clay; granite; sustainability; compressive strength; physical tests